1998
DOI: 10.1159/000006821
|View full text |Cite
|
Sign up to set email alerts
|

Separate Origins of All Three Major Coronary Arteries from the Right Sinus of Valsalva:A Rare Coronary Artery Anoma ly

Abstract: The origination of all three major coronary arteries from three separate ostia in the right sinus of Valsalva is an exceedingly rare coronary anomaly. Few radiographic and clinical details of this anomaly are available in the literature. We describe this anomaly in a patient with acute myocardial infarction who remained asymptomatic until the 8th decade of her life. Atherosclerotic narrowing of the normally originating right coronary artery caused the acute myocardial infarction. Anomalous left anterior descen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…3). A review of the literature revealed only 19 cases with this type of coronary anomaly (table 1)[ 1, 3,6,7,8,9,10,11,12,13,14,15,16,17,18]. Coronary artery disease was rarely detected in arteries with ectopic origin.…”
Section: Discussionmentioning
confidence: 99%
“…3). A review of the literature revealed only 19 cases with this type of coronary anomaly (table 1)[ 1, 3,6,7,8,9,10,11,12,13,14,15,16,17,18]. Coronary artery disease was rarely detected in arteries with ectopic origin.…”
Section: Discussionmentioning
confidence: 99%
“…[3] described a 61-year-old female with chest pain syndrome without atherosclerotic disease. Rahmatullah et al [4] described an 81-year-old female who presented with a non-Q-wave MI that had significant atherosclerotic disease in the normally positioned right coronary artery. Our 66-year-old patient had nonobstructive atherosclerotic coronary disease.…”
Section: Discussionmentioning
confidence: 99%
“…A far less common abnormality is that of all three coronary arteries arising from separate ostia within the right coronary cusp. This malformation has been described but thrice in the literature [2][3][4]. Though the entire coronary system arises from the right coronary cusp, the approach to such patients and the recommended similarities/differences to that of the left main arising from the right cusp has not been described.…”
Section: Introductionmentioning
confidence: 99%
“…Dear Sir, I read with interest the case report of separate origins of all three coronary arteries from the right coronary sinus by Rahmatullah et al [1]. Although the patient suffered an acute inferolateral myocardial infarction from obstructive diseases in the normally arising right coronary artery, the authors discussed the different mechanisms that an anomalous coronary artery may cause myocardial ischemia, myocardial infarction and sudden death, including a high take-off of an anomalous coronary artery.…”
mentioning
confidence: 99%
“…Although the patient suffered an acute inferolateral myocardial infarction from obstructive diseases in the normally arising right coronary artery, the authors discussed the different mechanisms that an anomalous coronary artery may cause myocardial ischemia, myocardial infarction and sudden death, including a high take-off of an anomalous coronary artery. According to Rahmatullah et al [1], the normal anatomical location of coronary ostia in sinuses of Valsalva permits the maximum diastolic coronary filling, but a high take-off of coronary artery in the tubular portion of the aorta may limit coronary perfusion.…”
mentioning
confidence: 99%